Cognitive behaviour therapy for stuttering - Lowe, Robyn (Henry Stewart Talks, 2019)
Negative thoughts, emotional and physiological reactions and their effect on behaviour is important for people who stutter, Adults seeking treatment for stuttering might develop mental health disorders, specifically social anxiety disorder, Cognitive behaviour therapy is the best treatment for social anxiety disorder, A cognitive behaviour therapy package was developed, Results of face-to-face and an internet version of that treatment package